Synthesis of bioactive glass-based coating by plasma electrolytic oxidation: Untangling a new deposition pathway toward titanium implant surfaces - Costa, Raphael C.; Souza, João G.S.; Cordeiro, Jairo M.; Bertolini, Martinna; de Avila, Erica D. [UNESP]; Landers, Richard; Rangel, Elidiane C. [UNESP]; Fortulan, Carlos A.; Retamal-Valdes, Belén; da Cruz, Nilson C. [UNESP]; Feres, Magda; Barão, Valentim A.R. (Elsevier, 2020)
Hypothesis: Although bioactive glass (BG) particle coatings were previously developed by different methods, poor particle adhesion to surfaces and reduced biological effects because of glass crystallization have limited their biomedical applications. To overcome this problem, we have untangled, for the first time, plasma electrolytic oxidation (PEO) as a new pathway for the synthesis of bioactive glass-based coating (PEO-BG) on titanium (Ti) materials. Experiments: Electrolyte solution with bioactive elements (Na2SiO3-5H2O, C4H6O4Ca, NaNO3, and C3H7Na2O6P) was used as a precursor source to obtain a 45S5 bioglass-like composition on a Ti surface by PEO. Subsequently, the PEO-BG coating was investigated with respect to its surface, mechanical, tribological, electrochemical, microbiological, and biological properties, compared with those of machined and sandblasted/acid-etched control surfaces. Findings: PEO treatment produced a coating with complex surface topography, Ti crystalline phases, superhydrophilic status, chemical composition, and oxide layer similar to that of 45S5-BG (~45.0Si, 24.5 Ca, 24.5Na, 6.0P w/v%). PEO-BG enhanced Ti mechanical and tribological properties with higher corrosion resistance. Furthermore, PEO-BG had a positive influence in polymicrobial biofilms, by reducing pathogenic bacterial associated with biofilm-related infections. PEO-BG also showed higher adsorption of blood plasma proteins without cytotoxic effects on human cells, and thus may be considered a promising biocompatible approach for biomedical implants.
Keywords: Bioactive coatings; Bioactive glass; Biofilms; Biomaterials; Corrosion; Dental implant; Plasma electrolytic oxidation; Proteins; Surface modification; Titanium